Pengaruh Brand Ambassador dan Brand Awareness terhadap Keputusan Pembelian Susu Merek Ultra Milk dengan Moderasi Brand Image (Studi Pada Konsumen Susu Merek Ultra Milk) : Penelitian - Isna Wardah Hasanah; Egi Radiansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of consumption trends and the popularity of Korean culture encourage companies to implement more creative and relevant marketing strategies, including through the use of brand ambassadors and increasing brand awareness. This study aims to analyze the influence of Brand Ambassador and Brand Awareness on Purchasing Decisions for the Ultra Milk brand, as well as to determine the role of Brand Image as a moderating variable. The study used a quantitative approach with a survey method through a questionnaire to 133 respondents. Data were analyzed using Structural Equation Modeling (SEM-PLS) with SmartPLS 4.1.0.9 software. The results showed that Brand Ambassador had a positive and significant effect on Purchasing Decisions (T = 2.364; P = 0.002), as well as Brand Awareness (T = 5.492; P = 0.000). However, Brand Image did not moderate the relationship between Brand Ambassador and Brand Awareness with Purchasing Decisions (coefficient -0.001; P = 0.995 and -0.023; P = 0.801). These findings indicate that the use of public figures and increased brand awareness are the main factors influencing consumer decisions in purchasing Ultra Milk products, although Brand Image does not strengthen the relationship.